The perception on the external factors that influence bully habit of students at secondary schools: Case study: SMK Tunku Mahmood, Batu Pahat Johor / Suhada Mokhtar and Norhayati Yusof - Mokhtar, Suhada; Yusof, Norhayati (Faculty of Administrative Science and Policy Studies, 2013)
Bully is defined as the frequent, persistent and intentional use of physical harm or intimidation by one child or a group of children to victimize another child (Salkind, 2005). Nowadays, bully becomes one of the popular issues in our country. This issue is starting getting attention of public when many videos of bully that happened at secondary school were uploading at mass media. Bully is can lead to various problems that can affect mental and physical of youth including students. Youth are future human capital of nation. Thus, it is important to all parties such as government, NGOs, parent, community and so forth to overcome this problem from becoming worse. In this research, there are several factors that can influence student to commit bully at school area. The factors are family, school, peers and mass media. So, this research is conduct to find out the relationship between the factors and bully behavior of student. It is show that lots of suggestions from this research and might useful for future improvement. As for this research, the researcher had conducted a study at Sekolah Menengah Kebangsaan Tunku Mahmood, Batu Pahat, Johor. There are 108 respondents out of 150 secondary students from Form 5 and Form 6 had been chosen for this study.